Association between magnesium depletion score and prevalence and all-cause mortality of psoriasis among the US population - Qi, Lin; Yang, Xian (Frontiers in Nutrition, 2025)
BackgroundMagnesium plays a key role in the physiopathologic process of psoriasis. The recently proposed magnesium depletion score (MDS) represents a comprehensive index for assessing magnesium status. However, the effect of MDS on psoriasis remains to be elucidated. This study aimed to evaluate the possible association between MDS and psoriasis prevalence and mortality.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) of adult participants. The multivariable logistic regression analysis was employed to assess the relationship between MDS and psoriasis prevalence. Restricted cubic splines (RCS) were utilized to investigate the dose–response correlation. Furthermore, Cox regression analysis was performed to determine the relationship between MDS and all-cause mortality in psoriasis patients. Furthermore, we conducted subgroup and sensitivity analyses to verify the validity and consistency of these results.ResultsThis study enrolled 17,883 eligible participants. After excluding individuals without follow-up information, 64 all-cause deaths were observed among 505 patients with psoriasis. In the weighted multivariable logistic regression model, individuals with an MDS ≥ 3 had a 1.75-fold greater risk of psoriasis compared with those with an MDS of 0 (OR = 1.75; 95% CI: 1.05–2.92; p < 0.05). RCS analysis revealed a positive linear relationship between MDS and psoriasis prevalence (P for nonlinear = 0.145). Additionally, Cox regression analysis demonstrated that MDS was positively associated with all-cause mortality (HR = 1.39; 95% CI: 1.04–1.87; p < 0.05). Subgroup analyses indicated that these findings remained consistent across different subgroups.ConclusionMDS is associated with an increased prevalence and all-cause mortality from psoriasis among American adults. Early detection and management for MDS may reduce the risk of psoriasis and improving its prognosis.